Population-specific call order in chimpanzee greeting vocal sequences - Cédric Girard-Buttoz; Tatiana Bortolato; Marion Laporte; Mathilde Grampp; Klaus Zuberbühler; Roman M. Wittig; Catherine Crockford (iScience, 2022)
Summary: Primates rarely learn new vocalizations, but they can learn to use their vocalizations in different contexts. Such “vocal usage learning,” particularly in vocal sequences, is a hallmark of human language, but remains understudied in non-human primates. We assess usage learning in four wild chimpanzee communities of Taï and Budongo Forests by investigating population differences in call ordering of a greeting vocal sequence. Whilst in all groups, these sequences consisted of pant-hoots (long-distance contact call) and pant-grunts (short-distance submissive call), the order of the two calls differed across populations. Taï chimpanzees consistently commenced greetings with pant-hoots, whereas Budongo chimpanzees started with pant-grunts. We discuss different hypotheses to explain this pattern and conclude that higher intra-group aggression in Budongo may have led to a local pattern of individuals signaling submission first. This highlights how within-species variation in social dynamics may lead to flexibility in call order production, possibly acquired via usage learning.